PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP PEMAHAMAN KONSEP BIOLOGI DAN SIKAP ILMIAH PESERTA DIDIK SMA NEGERI 3 TAKALAR - Endang Ayu Patrianingsih; Nurhayati B; Ernawati S Kaseng (UNM Journal of Biological Education, 2017)
The research is a quasi-experimental research with a non-equivalent research design of pretest posttest control group design. This study aimed to determine the differences in understanding the concept of Biology and scientific attitudes among learners who learn through discovery learning model and direct instruction. The study population were all science major students in grade XI Senior High School 3 Takalar registered in academic year 2015/2016. The samples were taken by simple random sampling technique. The data were collected by using a two tier multiple choice test and a scientific attitude questionnaire. The data were analyzed by descriptive analysis and MANOVA test. The results showed that learners who learned with discovery learning model has an understanding of Biology concepts in low category and scientific attitude in very good category. Meanwhile, learners who learned through direct instruction have an understanding of Biology concepts in very low category and a scientific attitude in good category. The result of statistical analysis showed that there are differences between the understanding of biology concepts and the scientific attitude among learners who learned through discovery learning model and direct instruction learning model (F = 10.450; Sig (0.000) <α).